2016
DOI: 10.1016/j.hrthm.2015.09.028
|View full text |Cite
|
Sign up to set email alerts
|

Association of left atrial function with incident atypical atrial flutter after atrial fibrillation ablation

Abstract: Background Symptomatic left atrial (LA) flutter (LAFL) is common following atrial fibrillation (AF) ablation. Objective To examine the association of baseline LA function with incident LAFL following AF ablation. Methods The source cohort included 216 patients with cardiac magnetic resonance (CMR) prior to initial AF ablation between 2010 and 2013. Patients who underwent cryoballoon or laser ablation, patients with AF during CMR, and those with suboptimal CMR, or missing follow-up data were excluded. Basel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 31 publications
0
7
0
Order By: Relevance
“…When circumferential pulmonary vein ablation includes lines, the prevalence is clearly higher in all studies, ranging from 10 to 31%. Lines were recently confirmed to be a predictive factor of LAT after atrial fibrillation ablation …”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…When circumferential pulmonary vein ablation includes lines, the prevalence is clearly higher in all studies, ranging from 10 to 31%. Lines were recently confirmed to be a predictive factor of LAT after atrial fibrillation ablation …”
Section: Discussionmentioning
confidence: 97%
“…Persistent atrial fibrillation, additional linear lesions in the LA, ablation gaps, and left atrial function have been identified as predictors of AT after RF ablation. Persistent atrial fibrillation was not a predictor in our study.…”
Section: Discussionmentioning
confidence: 99%
“…The reported experience of using FT-CMR LA strain parameter assessment for clinical diagnosis is quite recent, and encompasses cohorts of patients undergoing atrial fibrillation catheter ablation [ 8 , 47 , 48 ], implantable cardioverter-defibrillator implant [ 47 , 49 ], community volunteers without cardiovascular disease at baseline [ 50 , 51 ], patients with acute myocarditis [ 45 ], obesity [ 52 ], and Ebstein’s anomaly [ 53 ]. These studies established the feasibility and validity of LA strain parameter measurement using CMR; and in [ 51 ] found negative correlation between LA strain and LA fibrosis.…”
Section: Discussionmentioning
confidence: 99%
“…Left atrial tachycardia most commonly occurs after previous cardiac surgery or catheter ablation of atrial fibrillation (AF), but it can also be idiopathic. The reported prevalence of AT after AF catheter ablation (CA) ranges from 2% to 20% [3][4][5] and is mostly associated with structural heart disease [3]. Although external cardioversion (CV) and medical rate control are recommended by the recent ACC/AHA/HRS guidelines for acute treatment, relapse rates after CV are high [6].…”
Section: Introductionmentioning
confidence: 99%